Evaluasi Rasionalitas Peresepan Obat Berdasarkan Indikator World Health Organization (WHO) di Puskesmas “X” Yogyakarta - Yuni Andriani; Desinta Putri Kusuma; Nadia Husna (Lumbung Farmasi: Jurnal Ilmu Kefarmasian, 2025)
Rational use of drugs is when patients get the right drugs with their clinical needs such as the right dose, right duration of administration, and the lowest cost of treatment. Based on the World Health Organization (WHO) report, more than 50% of drug prescribing in the world has not been rational, the impact includes unwanted side effects to bacterial resistance to antibiotics. Prescribing indicators according to the WHO can be used to evaluate the rational use of drugs. This study aims tofind out the rationality of prescribing drugs in Puskesmas based on WHO indicators. This study is an observational descriptive studywith a cross-sectional approach. The data used in this study were prescriptions for February, May and December 2022 which were collected retrospectively. The results  of this study showed that most of the patients treated at Puskesmas "X" were female as many as 76 patients (69.09  %), aged at most 45-59 years as many as 44 patients (40.00%) and used BPJS PBI guarantee status as many as 46 patients (41.82%). The distribution of the most common diseases is essential (primary) hypertension as many as 11 diagnoses (10.00%), the most widely prescribed drugs class of analgesic-antipyretic drugs as many as 41 prescriptions (14.09%) in Paracetamol drugs as many as 37 prescriptions. Evaluation of the rationality of drug prescribing showed results that did not meet WHO standards, namely the average drug item per ep res sheet  was 2.65 items and the percentage of antibiotic drug prescribing was 24.55